2019
DOI: 10.4236/jbm.2019.72003
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Locations of Death and Factors Associated with Death among Cancer Patients in South Korea

Abstract: Background: Location of death has been used to examine an indicator for good death. This study aims to examine location of death among patients with three major cancers (gastric, liver, and lung) and other factors associated with location of death in South Korea. Methods: We selected the medical and pharmacy claims data for health services and location of death among the 42,596 decedents with cancer (lung 16,632, liver 15,872, gastric 10,092) from 2009 to 2013. We used logistic regressions to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that there was no correlation between sex [ 24 , 25 , 26 ] and the preferred place of care. However, another study reported that female patients with cancer were more likely to be discharged home than male patients [ 10 ]. In line with these findings, our study found that female patients were more likely to be discharged home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that there was no correlation between sex [ 24 , 25 , 26 ] and the preferred place of care. However, another study reported that female patients with cancer were more likely to be discharged home than male patients [ 10 ]. In line with these findings, our study found that female patients were more likely to be discharged home.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that 50–90% of patients with cancer wished to be cared for or die at home [ 9 ]. However, 87.2% of patients with terminal cancer spent time in a hospital at the EOL [ 10 ]. To respect the patient’s preference, it is important to know the barriers against achieving care at home at the EOL.…”
Section: Introductionmentioning
confidence: 99%